Indigenous Men Adhering to Highly Active Antiretroviral Therapy: Navigating Through Culturally Unsafe Spaces While Caring for Their Health - Chongo, Meck; Lavoie, Josée G.; Mignone, Javier; Caron, Nadine R.; Harder, Henry G.; Chase, Rob (Frontiers in Public Health, 2020)
Introduction: Indigenous peoples in Canada have endured and continue to experience the impact of colonization by European settlers. The deleterious manifestations of intergenerational historic trauma (HT) are evidenced in the high HIV/AIDS epidemic-related premature mortality rates among Indigenous men, despite the availability of novel highly active antiretroviral therapies (HAARTs). Aim: The aims of this study were to explore the impact of historic trauma (HT) on treatment adherence and health promoting practices among Indigenous men living with HIV, and how resilience was both expressed and mediated by survivor status. Methods: This interpretive description study incorporated a cultural safety lens. Through partnership with the Vancouver Native Health Society, 36 male HT survivors were recruited using purposive and theoretical sampling. They told their lived experiences and health promoting practices with respect to HAART adherence through interviews and a focus group. Results: Two broad categories (findings) emerged: (1) resilience as facilitator of HAART adherence; and (2) differential views on HT's impact. Resilience was expressed through nine concepts. Conclusion: Most Indigenous men in this study demonstrate health promoting behavior, stay on HAART and have better health and well-being even if the environments they live in are marginalized or heavily stigmatizing. This study shows that areas of strength and adaptation, including factors promoting resilience can be harnessed to foster HAART adherence. With a consideration of these areas of strength and adaptation, this study offers implications for research and recommendations to improve treatment-adherent behavior, fostering healing from HT, and reducing HIV/AIDS-related deaths.